A qualitative study of what motivates and enables climate-engaged physicians in Canada to engage in health-care sustainability, advocacy, and action. Issue 2 (February 2023) - Luo, Owen Dan; Razvi, Yasmeen; Kaur, Gurleen; Lim, Michelle; Smith, Kelti; Carson, Jacob Joel Kirsh; Petrin-Desrosiers, Claudel; Haldane, Victoria; Simms, Nicole; Miller, Fiona A
Summary: Increasing numbers of health-care professionals are aware of the need to deliver low-carbon sustainable health systems. We aimed to explore how physicians can be motivated and supported to pursue this ambition by conducting an exploratory qualitative descriptive study that involved individual in-depth interviews with climate-engaged Canadian physicians participating in health-care sustainability advocacy and action. Interview transcripts were analysed to identify themes related to the actions that physicians can take to promote sustainable health care, and the motivators and enablers of physician engagement in sustainable health care. Participants (n=19) engaged in a spectrum of health-care sustainability initiatives ranging from reducing health-care waste to lobbying and political action. They were motivated to advance health-care sustainability by their concern about the health implications of climate change, frustration with health-care waste, and recognition of their locus of influence as physicians. Participants articulated that policy and system, organisational and team, and knowledge generation and translation supports are required to strengthen their capacity to advance health-care sustainability. These findings can provide inspiration for engagement opportunities in health-care sustainability, guide service delivery and educational innovations to promote health-care professionals' interest in becoming sustainability champions, and extend the capacity of health-care professionals to reduce the climate impact of health care.